New hardening processes for transmission synchroniser hubs. (27th May 2017) - Akiyama, Yuu; Tokuoka, Terukazu; Terai, Hiroaki; Adachi, Yuuki; Amano, Nobuya
ABSTRACT: Synchroniser hubs are powder metal components often used in vehicles for manual transmissions and dual clutch transmissions. Conventionally, these components are often through hardened, case carburised or induction hardened, although such processes can lead to deterioration of dimensional accuracy and increased costs. Synchroniser hubs which have both high strength and high dimensional accuracy are developed by optimising the material composition and introducing the newly developed roller-hearth-type high temperature sintering furnace. Besides, a laser hardening process can be applied locally to the necessary portion. Furthermore, the second whole hardening process and extra process cost can be eliminated using sinter-hardening process after high-temperature sintering.